Terrestrial salamander abundance on reclaimed mountaintop removal mines - Petra Bohall Wood; Jennifer M. Williams (Wildlife Society Bulletin)
ABSTRACT Mountaintop removal mining, a large‐scale disturbance affecting vegetation, soil structure, and topography, converts landscapes from mature forests to extensive grassland and shrubland habitats. We sampled salamanders using drift‐fence arrays and coverboard transects on and near mountaintop removal mines in southern West Virginia, USA, during 2000–2002. We compared terrestrial salamander relative abundance and species richness of un‐mined, intact forest with habitats on reclaimed mountaintop removal mines (reclaimed grassland, reclaimed shrubland, and fragmented forest). Salamanders within forests increased in relative abundance with increasing distance from reclaimed mine edge. Reclaimed grassland and shrubland habitats had lower relative abundance and species richness than forests. Characteristics of reclaimed habitats that likely contributed to lower salamander abundance included poor soils (dry, compacted, little organic matter, high rock content), reduced vertical structure of vegetation and little tree cover, and low litter and woody debris cover. Past research has shown that salamander populations reduced by clearcutting may rebound in 15–24 years. Time since disturbance was 7–28 years in reclaimed habitats on our study areas and salamander populations had not reached levels found in adjacent mature forests. Published 2013. This article is a U.S. Government work and is in the public domain in the USA.